A balancing act: finding harmony between institutional needs and user feedback during a website redesign. Issue 2 (3rd April 2021) - Johnson, Shannon; Mann, Erika; Marshall, Ann; Rupp, Nathan; Wagner, Sarah
Abstract: In this column, an academic library's web team shares their experience of managing a website redesign while also navigating institutional changes and branding requirements. They detail the obstacles and challenges that needed to be managed in order to build a new website with limited staff and technological resources to better meet the needs of library users.